Security in device‐to‐device communications: a survey. Issue 1 (1st January 2018) - Nait Hamoud, Othmane; Kenaza, Tayeb; Challal, Yacine
Abstract : Device‐to‐device (D2D) communication is a promising technology for the next generation mobile communication networks (5G). Indeed, it is expected to allow high throughput, reduce communication delays and reduce energy consumption and traffic load. D2D technology will enhance the capacity and the performance of traditional cellular networks. Security issues must be considered in all types of communications, especially when it comes to wireless communication between devices involved in controlling critical infrastructures and/or dealing with personal data. The authors propose taxonomy based on the review of recent works which have addressed the security issues in D2D communications. This taxonomy is more practical since it gives, on the one hand, a better readability and a good understanding of all the works that have addressed the security issues in the literature, and on the other hand, a roadmap towards a global security solution that combines the best techniques and security solutions inherent to each layer: physical, MAC, network and application.